A gas diffusion layer and a preparation method thereof and a fuel cell made therefrom

By etching the hydrophilic layer of the gas diffusion layer to form hydrophilic spots, the problem of difficult membrane electrodes in low humidity environments and easy flooding in high humidity environments is solved, and high-performance applications under different humidity conditions are achieved .

CN118572127BActive Publication Date: 2025-02-11CAS LINKFIBER NEW MATERIALS (CHANGZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410731982.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-02-11
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The existing gas diffusion layer is difficult to maintain wet in a low-humidity environment, resulting in a degradation of membrane electrode performance; it is prone to flooding in a high-humidity environment, hindering the passage of reaction gas.

Method used

The structure of the base layer-hydrophilic layer-hydrophobic layer is adopted and etched in the hydrophilic layer to form discontinuous hydrophilic spots and are distributed in the area corresponding to the bipolar plate flow channel.

Benefits of technology

In low humidity environment, the hydrophilic site effectively adsorbs water molecules, keeping the proton exchange membrane moist, and improving the proton conductivity and conductivity of the membrane electrode; in high humidity environment, the hydrophilic site preferentially absorbs water to avoid flooding. Ensure the passage of the reaction gas is unobstructed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118572127B_ABST
    Figure CN118572127B_ABST
Patent Text Reader

Abstract

The present invention provides a gas diffusion layer, a preparation method thereof, and a fuel cell made therefrom. The gas diffusion layer comprises a base layer, a hydrophilic layer, and a hydrophobic layer connected in sequence; the hydrophilic layer comprises a plurality of discontinuous hydrophilic sites, and the hydrophilic sites are distributed in an area corresponding to the bipolar plate flow channel of the fuel cell membrane electrode. The preparation method thereof is as follows: a hydrophilic slurry is configured, and an initial hydrophilic layer is coated on the base layer; a hydrophilic site pattern is designed according to the bipolar plate flow channel, and the initial hydrophilic layer is etched with laser rays to obtain a hydrophilic layer; a hydrophobic slurry is configured, and a hydrophobic layer is coated on the hydrophilic layer; and the above-mentioned obtained product is sintered to obtain. The present invention effectively solves the problem of difficulty in retaining moisture under low humidity and easy flooding under high humidity by preparing a base layer-hydrophilic layer-hydrophobic layer structure and etching the hydrophilic layer to obtain the hydrophilic sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a gas diffusion layer and a preparation method thereof, and a fuel cell made therefrom. Background Art

[0002] Hydrogen fuel cell is an energy conversion device that directly converts chemical energy into electrical energy. It has the advantages of high energy density, high utilization rate, clean and quiet, and is an efficient energy conversion device. Among them, proton exchange membrane fuel cell is the most widely used. Its core component is membrane electrode, which is the multiphase material transfer and electrochemical reaction site for energy conversion. It involves three-phase interface reaction and complex mass transfer and heat transfer process, which directly determines the performance, life and cost of fuel cell. Membrane electrode is composed of proton exchange membrane, catalyst, gas diffusion layer, bipolar plate and other structures. Its typical assembly scheme is as follows: first prepare proton exchange membrane, spray catalyst slurry on both sides of proton exchange membrane anode and cathode, and form a structure of catalyst layer on proton exchange membrane; coat microporous layer on the surface of carbon paper substrate to form gas diffusion layer; according to the order of cathode gas diffusion layer, proton exchange membrane sprayed with catalyst, and anode gas diffusion layer, they are respectively packaged between the bipolar plates on both sides, and packaged by gaskets and bolts to form a single-layer membrane electrode structure.

[0003] The gas diffusion layer can be prepared by coating a microporous layer on one side of a porous carbon paper or carbon cloth as a substrate. The gas diffusion layer has the functions of providing gas channels, drainage channels, and effective carrier channels for electrode reactions on the one hand; on the other hand, it can support the catalyst and stabilize the electrode structure. The gas diffusion layer is a typical "one material for multiple uses" material. Different functions require different structural performance parameters, so there is a trade-off effect in performance regulation.

[0004] The bipolar plate is another core component of the fuel cell. Its main function is to support the membrane electrode, provide hydrogen, oxygen and coolant fluid channels, separate hydrogen / oxygen, collect electrons, and conduct heat. The core area of ​​the bipolar plate is the flow field area. Its structure is to form a number of interconnected grooves on the graphite or metal surface to form a flow channel for the reaction gas conduction and facilitate the discharge of the reaction product water; while the non-flow channel area is closely attached to the gas diffusion layer, which can effectively support the membrane electrode and conduct electrons and heat.

[0005] There are at least two technical problems:

[0006] First of all, in the membrane electrode, the proton exchange membrane not only has a barrier function, but also has the function of conducting protons. Under low humidity or high temperature conditions, its electrical conductivity is easily reduced due to lack of water, which affects the proton conduction efficiency and causes the membrane electrode performance to decline, which will directly affect the reaction efficiency of hydrogen fuel cells.

[0007] Secondly, during the operation of the fuel cell, water is generated as a reaction product on the cathode side, and some liquid water is discharged from the bipolar plate flow channel along with the reaction gas flow, and is also transferred to the anode side due to reverse diffusion. Under high humidity or high current density conditions, the water generation rate may be greater than the discharge and diffusion rate, and the excess water will remain inside the battery, blocking the pore space of the gas diffusion layer, and the reactants hydrogen and oxygen cannot fully enter the catalyst layer, thus forming a "flooded" state.

[0008] In order to solve the problem of poor performance of hydrogen fuel cell membrane electrode under low humidity environment, different interlayer hydrophilic layers are added during the coating process of microporous layer hydrophobic layer, and the hydrophilic layer effectively adsorbs water molecules to improve the moisture retention performance of membrane electrode under low humidity environment. Journal "Hydrophilic and hydrophobic double microporous layer coated gas diffusion layer for enhancing performance of polymer electrolyte fuelcells under no-humidifification at the cathode, Journal of Power Sources, 199 (2012): 29–36" A new type of hydrophilic and hydrophobic double microporous layer coated gas diffusion layer was developed to further improve the performance of fuel cells under no-humidification conditions at the cathode. A hydrophobic MPL composed of carbon black and polytetrafluoroethylene was coated on a carbon paper substrate; a hydrophilic layer composed of carbon black and polyvinyl alcohol was also coated on the hydrophobic gas diffusion layer. The hydrophilic layer can effectively maintain the humidity of the catalyst layer, while the hydrophobic interlayer between the hydrophilic layer and the substrate prevents the removal of water in the hydrophilic layer by dry air in the substrate. Patent CN202210088485.9 discloses a fuel cell gas diffusion layer and a preparation method thereof, wherein the gas diffusion layer includes a carbon fiber base layer and a microporous layer, and the gas diffusion layer includes a hydrophilic polymer, which improves the water retention effect of the gas diffusion layer, so that the gas diffusion layer has a self-humidifying function. The hydrophilic polymer is combined with polytetrafluoroethylene to repel the gas diffusion layer, so that the gas diffusion layer does not need to be equipped with a water cooling system and a humidification system.

[0009] Although these methods described above can partially solve some problems of the gas diffusion layer, they cannot take into account the gas diffusion layer's needs for low humidity moisture retention to improve activity and high humidity drainage to prevent flooding.

[0010] In view of this, the present invention is proposed. Summary of the invention

[0011] The purpose of the present invention is to provide a gas diffusion layer, a preparation method thereof and a fuel cell made therefrom, by preparing a structure of a base layer-hydrophilic layer-hydrophobic layer and etching the hydrophilic layer to obtain hydrophilic sites, thereby effectively solving the problem of difficulty in retaining moisture under low humidity and easy flooding under high humidity.

[0012] To achieve the above objectives, the present invention adopts the following specific technical solutions:

[0013] In a first aspect, the present invention provides a gas diffusion layer, comprising a base layer, a hydrophilic layer and a hydrophobic layer connected in sequence; the hydrophilic layer comprises a plurality of discontinuous hydrophilic sites, and the hydrophilic sites are distributed in an area corresponding to a bipolar plate flow channel of a fuel cell membrane electrode.

[0014] In a second aspect, the present invention further provides a method for preparing a gas diffusion layer, comprising the following steps:

[0015] S1: preparing a hydrophilic slurry and coating an initial hydrophilic layer on the base layer to form an initial hydrophilic layer.

[0016] S2: Designing a hydrophilic site pattern according to the bipolar plate flow channel of the fuel cell membrane electrode, and using the pattern to etch the initial hydrophilic layer with laser rays to obtain a hydrophilic layer including the hydrophilic sites and the etched area.

[0017] S3: preparing a hydrophobic slurry, and coating a hydrophobic layer on the hydrophilic layer to form a hydrophobic layer.

[0018] S4: Sintering the product obtained in step S3 to obtain the gas diffusion layer.

[0019] In a third aspect, the present invention further provides a fuel cell, comprising the gas diffusion layer or the gas diffusion layer prepared by the preparation method.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] (1) When the membrane electrode made of the gas diffusion layer of the present invention is used in a low humidity environment, the water generated by the adsorption reaction and the water brought by the reverse diffusion are easily adsorbed in the hydrophilic sites, and the proton exchange membrane is more easily maintained in a humid environment, thereby maintaining the activity of the proton exchange membrane, improving the proton conductivity and electrical conductivity of the proton exchange membrane, and thus improving the power density of the hydrogen fuel cell.

[0022] (2) When the membrane electrode made of the gas diffusion layer of the present invention is used in a high humidity environment and at a high current density, a large amount of water is generated by the reaction. This water will preferentially enter the hydrophilic site and be discharged to the bipolar plate flow channel through the pores of the carbon paper. The area outside the hydrophilic site is not affected by the drainage, and the pore structure is not easily blocked by water. The reaction gas can pass through unimpeded and reach the catalyst layer, thereby improving the performance of the membrane electrode in a high humidity environment.

[0023] In summary, the gas diffusion layer prepared by the present invention and its assembly method can effectively improve the performance of the gas diffusion layer in different application scenarios, achieve moisture retention and efficiency enhancement in a low-humidity environment, and water drainage and "flooding prevention" in a high-humidity environment. It can take into account the application in both high and low humidity scenarios at the same time, and effectively expand the scope of high-performance use of hydrogen fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0025] Figure 1 It is a cross-sectional schematic diagram of the initial hydrophilic layer after coating of the present invention.

[0026] Figure 2 Schematic top view of the hydrophilic site of the present invention.

[0027] Figure 3 Schematic diagram of a top view of the bipolar plate flow field area corresponding to the hydrophilic site of the present invention.

[0028] Figure 4 It is a cross-sectional schematic diagram of the laser etching of the hydrophilic layer of the present invention.

[0029] Figure 5 It is a cross-sectional schematic diagram of the hydrophobic layer after coating of the present invention.

[0030] Figure 6 Comparison of polarization curves of membrane electrodes prepared with gas diffusion layers of Example 1, Comparative Example 1 and Comparative Example 2 at 20% RH humidity.

[0031] Figure 7 Comparison of membrane electrode polarization curves of the membrane electrodes prepared with the gas diffusion layers of Example 1, Comparative Example 1 and Comparative Example 2 at 100% RH humidity.

[0032] Description of reference numerals:

[0033] 1-base layer; 2-hydrophilic layer; 3-hydrophobic layer; 4-laser ray; 5-hydrophilic site; 6-bipolar plate non-flow channel; 7-bipolar plate flow channel. DETAILED DESCRIPTION

[0034] As used herein:

[0035] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0036] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0037] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0038] In these embodiments, unless otherwise specified, the parts and percentages are all based on mass. The raw material ratios not specified in the present invention can be mixed in any ratio.

[0039] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0040] A gas diffusion layer of the present invention, see Figure 1-5 As shown, it includes a base layer 1, a hydrophilic layer 2 and a hydrophobic layer 3 connected in sequence; the hydrophilic layer 1 includes a plurality of discontinuous hydrophilic sites 5, and the hydrophilic sites 5 are distributed in the area corresponding to the bipolar plate flow channel 7 of the fuel cell membrane electrode.

[0041] The present invention provides a method for preparing a gas diffusion layer, comprising the following steps:

[0042] S1: Prepare hydrophilic slurry, such as Figure 1 As shown, an initial hydrophilic layer is coated on the base layer 1 to form an initial hydrophilic layer, corresponding to Figure 1The area of ​​the hydrophilic layer 2.

[0043] In some preferred embodiments, the base layer 1 is carbon paper that has been subjected to hydrophobic treatment; in some more preferred embodiments, the content of the hydrophobic agent in the carbon paper is 5% to 35%.

[0044] Furthermore, the hydrophilic slurry is prepared by dissolving carbon black powder and a hydrophilic agent in deionized water and homogenizing the mixture.

[0045] In some optional embodiments, the hydrophilic agent includes one or more of Tween, Span, hydroxypropyl methylcellulose (HPMC), polyethylene glycol (PEG) or polyvinyl alcohol (PVA).

[0046] In some preferred embodiments, the solid content of the hydrophilic slurry is 2-25%.

[0047] In some preferred embodiments, the mass ratio of the carbon black powder to the hydrophilic agent is (3-5):1.

[0048] S2: See Figure 2 and Figure 3 According to the bipolar plate flow channel 7 of the fuel cell membrane electrode, a hydrophilic site pattern is designed, and the initial hydrophilic layer is etched with laser beam 4 using the pattern, such as Figure 4 As shown, a hydrophilic layer including hydrophilic sites and etched areas is obtained.

[0049] In some preferred embodiments, the hydrophilic layer 2 includes a plurality of non-continuous hydrophilic sites 5 .

[0050] like Figure 3 As shown, the bipolar plate flow field region includes a bipolar plate non-flow channel 6 and a bipolar plate flow channel 7. In some preferred embodiments, see Figure 2 and Figure 3 The hydrophilic sites 5 of the hydrophilic layer 2 are all located in the area corresponding to the bipolar plate flow channel 7.

[0051] In some embodiments, the single hydrophilic site 5 is Figure 2 The quadrilateral shown may also be a circle or any other shape.

[0052] In some preferred embodiments, the area of ​​a single hydrophilic site 5 is 0.05-0.5 mm 2 .

[0053] In some preferred embodiments, the total area of ​​the hydrophilic sites 5 accounts for 5-40% of the area of ​​the bipolar plate flow channel 7 .

[0054] In some preferred embodiments, the energy density of the laser ray etching is 5-100 mJ / mm 2 .

[0055] S3: Prepare hydrophobic slurry, see Figure 5 As shown, a hydrophobic layer is coated on the hydrophilic layer 2 to form a hydrophobic layer 3 .

[0056] Furthermore, the hydrophobic slurry is prepared by dissolving carbon black powder and a hydrophobic agent in deionized water and homogenizing the mixture.

[0057] In some optional embodiments, the hydrophobic agent includes one or more of polytetrafluoroethylene (PTFE), polyperfluoroethylene propylene (FEP), ethylene tetrafluoroethylene copolymer (ETFE), soluble polytetrafluoroethylene (PFA) or polyvinylidene fluoride homopolymer (PVDF).

[0058] In some preferred embodiments, the solid content of the hydrophobic slurry is 5-30%.

[0059] In some preferred embodiments, the mass ratio of the carbon black powder to the hydrophobic agent is (2-4):1.

[0060] In some preferred embodiments, the coated hydrophobic layer is heat-treated by infrared thermal radiation heating, and the heat treatment temperature is controlled to be 80-120°C. Due to the uneven heating by infrared thermal radiation, an obvious temperature difference will be generated in the cross-sectional direction of the hydrophobic layer. Due to the difference in diffusion rate, the hydrophobic agent content in the hydrophobic layer forms a gradient structure during the drying process, that is, the hydrophobic agent content near the catalyst layer is relatively high; the hydrophobic agent content near the bipolar plate layer is relatively low. During the drainage process, liquid water will tend to be discharged outward along the hydrophobic gradient, which is more conducive to improving the reaction efficiency during battery operation.

[0061] S4: Sintering the product obtained in step S3 to obtain the gas diffusion layer.

[0062] Furthermore, the sintering temperature is 300-400° C., and the sintering time is 20-40 min.

[0063] In some optional embodiments, the thickness of the hydrophilic site 5 is 5-15 μm; and the total thickness of the hydrophilic layer 2 and the hydrophobic layer 3 is 25-35 μm.

[0064] The present invention also provides a fuel cell, comprising the gas diffusion layer or the gas diffusion layer prepared by the preparation method.

[0065] Example 1

[0066] A method for preparing a gas diffusion layer:

[0067] (1) Take carbon black and hydrophilic agent HPMC in a mass ratio of 4:1, slowly add the above two components into deionized water, disperse and stir in a high shear homogenizer for 20 minutes at a stirring speed of 5000 rpm, and take out to obtain a hydrophilic slurry with a solid content of 8%. The hydrophilic slurry is coated on a base layer with a hydrophobic agent content of 15% by a slit coater, and the coated microporous layer is dried to control the thickness of the hydrophilic microporous layer to 10 μm.

[0068] (2) According to the shape of the bipolar plate flow channel, the laser beam scanning pattern is designed so that the hydrophilic sites retained after laser scanning are located in the corresponding positions of the bipolar plate flow channel. The area of ​​a single hydrophilic site is 0.1 mm 2 The total hydrophilic site area accounts for 15% of the bipolar plate flow channel area. Then the gas diffusion layer is fixed under the laser beam and scanned and etched, and the energy density of the laser etching is controlled to 20mJ / mm 2 .

[0069] (3) Take carbon black and hydrophobic agent PTFE in a mass ratio of 3:1, slowly add the above two components into deionized water respectively; disperse and stir in a high shear homogenizer for 20 minutes at a stirring speed of 5000 rpm, and take out to obtain a hydrophobic slurry with a solid content of 15%. Use a slit coater to coat the hydrophobic microporous layer on the hydrophilic layer etched in step (2), and dry the coated microporous layer to control the total microporous layer thickness to 30 μm.

[0070] (4) The product obtained in step (3) is placed in an atmosphere furnace for high-temperature sintering at a temperature of 350° C. for 30 min, during which nitrogen is continuously introduced for protection, and the gas diffusion layer is taken out to obtain the gas diffusion layer.

[0071] The preparation methods of Examples 2-7 and Comparative Examples 1-2 are basically the same as those of Example 1, and the differences are shown in Table 1. Among them, the difference between Comparative Example 1 and Example 1 is that Steps (1) and (2) of Example 1 are not included, and only a hydrophobic layer is coated on the base layer and sintered. The difference between Comparative Example 2 and Example 1 is that Step (2) of Example 1 is not included, and a hydrophobic layer is coated on the unetched hydrophilic layer and sintered.

[0072] Table 1 Preparation parameter conditions of Examples 1-7 and Comparative Examples 1-2

[0073]

[0074] The samples in the embodiments and comparative examples were tested for performance:

[0075] The prepared gas diffusion layer is cut into the size corresponding to the bipolar plate, and the hydrophilic site is ensured to correspond to the position of the bipolar plate flow channel. The single-layer membrane electrode battery is assembled for performance testing, and the membrane electrode polarization curve is drawn according to the test results; the maximum power density of the battery is tested under the condition of relative humidity of 20% RH, wherein the polarization curves of Example 1 and Comparative Examples 1-2 are compared. Figure 6 As shown; Under the conditions of relative humidity 100% RH and voltage 0.3V, the power density of the battery was tested, wherein the polarization curves of Example 1 and Comparative Examples 1-2 were compared as Figure 7 In addition, the test results of power density are shown in Table 2. The battery test method refers to GB / T 20042.5-2009 Proton Exchange Membrane Fuel Cell Part 5: Membrane Electrode Test Method.

[0076] Comparative Example 1 Compared with Example 1, see Figure 6 and Figure 7 In a high humidity environment (100% RH), the polarization curves of the two devices are not much different, and the maximum power density can be maintained at 1.6W / cm 2 Above, especially at low voltage (<0.4V) and high current density (>4A / cm 2 ) stage, there was no obvious flooding, and the reaction gas mass transfer was sufficient, indicating that the hydrophobic structure of the microporous layer of both was reasonably designed, the pore channels of the substrate layer were smooth, the drainage performance was good, and the catalyst layer reacted fully. However, in a low humidity (20% RH) environment, the slope of the polarization curve of Comparative Example 1 decreased significantly, and the maximum power density was only 0.97W / cm 2 Since the hydrophilic layer structure is not set in Comparative Example 1, the performance of the proton exchange membrane is significantly reduced due to drying in a low humidity environment; while the effective hydrophilic sites are set in Example 1, which can keep the catalyst layer wet under low humidity conditions, significantly improve the power generation performance, and the maximum power density reaches 1.52W / cm 2 .

[0077] Comparative Example 2 is compared with Example 1. Figure 6 and Figure 7 In a low humidity (20% RH) environment, the polarization curves of the two devices are not much different, and the maximum power density can be maintained at 1.5W / cm 2 Because both of them are equipped with a hydrophilic microporous layer structure, the proton exchange membrane and the catalyst layer can maintain a stable humid environment, the humidity has little effect on the battery performance, the reaction is more complete, and the power generation performance does not decrease significantly. In a high humidity (100% RH) environment, as the voltage of Example 2 decreases, the current density continues to increase, and the water produced by the reaction gradually increases. Because its structure includes a continuous hydrophilic microporous layer, a large amount of water accumulates here, occupying the channel for the reaction gas transmission, and the slope of the polarization curve gradually decreases. At a voltage of 0.3V, the power density is only 1.08W / cm 2Although Example 1 is also designed with hydrophilic sites, it is a discontinuous form, and its area only accounts for 15% of the entire flow channel area. While ensuring the provision of effective drainage channels, it can also provide a large number of pore channels for the reaction gas conduction, effectively improving the reaction efficiency. At a voltage of 0.3V, the power density can reach 1.53W / cm 2 .

[0078] Compared with Example 1, in the process of battery power generation performance test, although the highest power density is basically the same, when working at low voltage, due to the increase of current density, the discharge of reaction water increases, and the drainage effect of Example 7 is more sufficient. At a voltage of 0.3V, the power density can reach 1.60W / cm 2 Its power generation performance is better, which mainly depends on the gradient structure formed by infrared thermal radiation on the hydrophobic layer, which is more conducive to the discharge of reaction product water and effectively improves the gas mass transfer effect under current density.

[0079] Table 2 Comparison of membrane electrode performance

[0080]

[0081] It can be seen from Table 2 that, whether in a low humidity (20% RH) environment or a high humidity (100% RH) environment, the power density of the hydrophilic sites obtained by etching is generally greater than that of the hydrophilic sites not etched. At the same time, the power density is further improved by heating the base layer and the hydrophilic layer to a certain temperature before coating the hydrophobic layer.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention is described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the above embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In addition, those skilled in the art can understand that although some embodiments herein include certain features included in other embodiments instead of other features, the combination of features of different embodiments means being within the scope of the present invention and forming different embodiments. For example, in the above claims, any one of the embodiments claimed for protection can be used in any combination. The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as admitting or suggesting in any form that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a gas diffusion layer, characterized in that: The steps include: S1: preparing a hydrophilic slurry and coating an initial hydrophilic layer on the base layer to form an initial hydrophilic layer; The hydrophilic slurry is prepared by dissolving carbon black powder and a hydrophilic agent in deionized water and homogenizing the mixture; the hydrophilic agent comprises one or more of Tween, Span, hydroxypropyl methylcellulose, polyethylene glycol or polyvinyl alcohol; the solid content of the hydrophilic slurry is 2-25%; the mass ratio of the carbon black powder to the hydrophilic agent is (3-5):1; S2: designing a hydrophilic site pattern according to the bipolar plate flow channel of the fuel cell membrane electrode, and etching the initial hydrophilic layer with laser rays using the pattern to obtain a hydrophilic layer including the hydrophilic site and the etched area; The hydrophilic layer includes a plurality of non-continuous hydrophilic sites; the hydrophilic sites of the hydrophilic layer are all located in the area corresponding to the bipolar plate flow channel; the total area of ​​the hydrophilic sites accounts for 5-40% of the area of ​​the bipolar plate flow channel; S3: preparing a hydrophobic slurry, and coating the hydrophobic layer on the hydrophilic layer to form a hydrophobic layer; The hydrophobic slurry is prepared by dissolving carbon black powder and a hydrophobic agent in deionized water and homogenizing the mixture; the hydrophobic agent comprises one or more of polytetrafluoroethylene, polyperfluoroethylene propylene, ethylene tetrafluoroethylene copolymer, soluble polytetrafluoroethylene or polyvinylidene fluoride homopolymer; the solid content of the hydrophobic slurry is 5-30%; the mass ratio of the carbon black powder to the hydrophobic agent is (2-4):1; S4: Sintering the product obtained in step S3 to obtain the gas diffusion layer.

2. The preparation method according to claim 1, characterized in that: In step S1, the base layer is carbon paper after hydrophobic treatment; The content of the hydrophobic agent in the carbon paper is 5% to 35%.

3. The preparation method according to claim 1, characterized in that: In step S2, the area of ​​a single hydrophilic site is 0.05-0.5 mm 2 ; The energy density of the laser ray etching is 5-100mJ / mm 2 .

4. The preparation method according to claim 1, characterized in that: In step S3, the coated hydrophobic layer is heat treated.

5. The preparation method according to claim 4, characterized in that: In step S3, the heat treatment is performed by infrared heat radiation heating.

6. The preparation method according to claim 4 or 5, characterized in that: In step S3, the temperature of the heat treatment is 80-120°C.

7. The preparation method according to claim 1, characterized in that: In step S4, the sintering temperature is 300-400° C., and the sintering time is 20-40 min.

8. The preparation method according to claim 1, characterized in that: The thickness of the hydrophilic site is 5-15 μm; The total thickness of the hydrophilic layer and the hydrophobic layer is 25-35 μm.

Citation Information

Patent Citations

  • A fuel cell gas diffusion layer and a preparation method thereof and a fuel cell

    CN114464834B

  • Gas diffusion layer with water retaining property for fuel cell, preparation method of gas diffusion layer, membrane electrode assembly and application

    CN103956505A

  • Fuel cell electrode in-situ preparation method based on microporous layer with double-layer ordered structure

    CN112382767A

  • Membrane electrode, fuel cell and vehicle

    CN113782752A